2017
DOI: 10.20338/bjmb.v11i1.99
|View full text |Cite
|
Sign up to set email alerts
|

The level of mental workload related to the index of difficulty of the motor task and handedness

Abstract: BACKGROUND: Manual movements are affected by the index of difficulty of the task and handedness. High index of difficulty and execution with the non-dominant hand can increase the mental workload.AIM: This study investigated the relation between the level of mental workload, the index of difficulty of the task, and handedness in manual movements.METHOD: Twenty-three right-handed male students (24.1 ± 4.3 years) participated in this study. The index of difficulty in the Grooved Pegboard task was manipulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Therefore, whether or not an individual's COMT genotype favors motor performance depends partly on the nature of the task to be performed (Tunbridge et al, 2006), such that greater asymmetry is associated with increased ID that demands greater information processing. Lelis-Torres et al (2017) showed, through electroencephalographic analyses, that the index of mental working load was higher under the place condition than under the remove condition of the Grooved Pegboard Test. As the mental working load is a function of the perceptual, cognitive, and motor task demands, there can also be expected differences between right-and left-hand performances of the same task (Lelis-Torres et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, whether or not an individual's COMT genotype favors motor performance depends partly on the nature of the task to be performed (Tunbridge et al, 2006), such that greater asymmetry is associated with increased ID that demands greater information processing. Lelis-Torres et al (2017) showed, through electroencephalographic analyses, that the index of mental working load was higher under the place condition than under the remove condition of the Grooved Pegboard Test. As the mental working load is a function of the perceptual, cognitive, and motor task demands, there can also be expected differences between right-and left-hand performances of the same task (Lelis-Torres et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…The greater asymmetry for participants during the place condition relative to the remove condition was expected, since the increased task difficulty and greater accuracy demands of the place condition have both been linked with greater lateral asymmetries (Bryden et al., 2007; Vasconcelos & Rodrigues, 2008). Prior studies using the Grooved Pegboard Test to investigate manual asymmetries showed a greater RT when placing the pegs (higher ID) than when removing the pegs (lower ID; Bryden & Roy, 2005; Fernandes, Souza, Sales, & Apolinário-Souza, 2018; Lelis-Torres et al., 2017; Salvador et al., 2017). This difference observed in right- and left-hand performance among these participants may have been attributable to contralateral hemisphere specialization for voluntary movement organization and control (Elliott & Roy, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Checking boxes by hand requires moving the pencil from box to box; a landmark study on such types of movement was written by Fitts in 1954, leading to them being called Fitts’s tasks. Movement time [ 17 , 18 ] and cognitive load [ 19 ] have been shown to increase alongside the Fitts task’s index of difficulty (ID), which is a log 2 function of the ratio between the distance between the two checkboxes (A) and the size of the checkbox (W) at the location of arrival; ID = log 2 (1 + A/W). The efficiency and usability of a checklist can be improved by reducing the ID of the pointing tasks; checkboxes should be of sufficient size and arranged such that they minimize the total travel path of the hand.…”
Section: Introductionmentioning
confidence: 99%